1998
DOI: 10.4269/ajtmh.1998.59.991
|View full text |Cite
|
Sign up to set email alerts
|

Passive transfer of growth-inhibitory antibodies raised against yeast-expressed recombinant Plasmodium falciparum merozoite surface protein-1(19).

Abstract: Abstract. Purified rabbit immunoglobulin raised against yeast-expressed recombinant FVO or 3D7 Plasmodium falciparum merozoite surface protein-1 (MSP-1) 19k-D C terminal fragment (MSP-1 19 ) was transfused into malarianaive Aotus nancymai monkeys that were immediately challenged with FVO asexual stage malaria parasites. Control monkeys received rabbit immunoglobulin raised against the sexual stage antigen Pfs25 or Aotus hyperimmune serum obtained from monkeys immunized by P. falciparum infection and drug cure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…We observed that of the four mice that received both T cells and rabbit anti-AMA1 antiserum, only one animal (mouse 2) developed a significant murine anti-AMA1 response. The transfused Abs may have suppressed the development of such a response, as was shown to occur in a different malaria system (25,26). The combination in nude mice of this passively administered CMI response with a passively administered anti-AMA1 Ab response gives rise to a degree of protection similar to that which follows AMA1 vaccination of euthymic mice (Fig.…”
Section: Discussionmentioning
confidence: 85%
“…We observed that of the four mice that received both T cells and rabbit anti-AMA1 antiserum, only one animal (mouse 2) developed a significant murine anti-AMA1 response. The transfused Abs may have suppressed the development of such a response, as was shown to occur in a different malaria system (25,26). The combination in nude mice of this passively administered CMI response with a passively administered anti-AMA1 Ab response gives rise to a degree of protection similar to that which follows AMA1 vaccination of euthymic mice (Fig.…”
Section: Discussionmentioning
confidence: 85%
“…Recombinant MSP-1 19 proteins corresponding to the four major described variants of MSP-1 19 (the Wellcome/K1 (E-TSR) and MAD20 (Q-KNG) alleles as well as the E-KNG and Q-TSR variants) were expressed in Saccharomyces cerivisiae (39), obtained from the Malaria Research and Reference Reagent Resource Center (Manassas, VA). The Wellcome/K1 and MAD20 alleles were also expressed in Escherichia coli as GST fusion proteins (40).…”
Section: Laboratory Studiesmentioning
confidence: 99%
“…This protection is largely antibody mediated (18,36). Aotus monkeys were protected from the virulent FVO strain of P. falciparum by immunization with MSP1 19 (12,15,34). MSP1 19 -specific antibodies confer passive immunity in rodent models (4,53) and inhibit merozoite invasion in vitro (2).…”
mentioning
confidence: 99%